Impact of seeing and host galaxy into the analysis of photo-polarimetric microvariability in blazars: Case study of the nearby blazars 1ES 1959+650 and HB89 2201+044 - Sosa, Marina Soledad (2017)
Blazars, a type of Active Galactic Nuclei, present a particular orientation of their jets close to the line of sight. Their radiation is thus relativistically beamed, giving rise to extreme behaviors, specially strong variability on very short timescales (i.e., microvariability). Here we present simultaneous photometric and polarimetric observations of two relatively nearby blazars, 1ES 1959+650 and HB89 2201+044, that were obtained using the Calar Alto Faint Object Spectrograph mounted at the 2.2 m telescope in Calar Alto, Spain. An outstanding characteristic of these two blazars is the presence of well resolved host galaxies. This particular feature allows us to produce a study of their intrinsic polarization, a measurement of the polarization state of the galactic nucleus unaffected by the host galaxy. To carry out this work, we computed photometric fluxes from which we calculated the degree and orientation of the blazars polarization. Then, we analyzed the depolarizing effect introduced by the host galaxy with the main goal to recover the intrinsic polarization of the galactic nucleus, carefully taking into consideration the spurious polarimetric variability introduced by changes in seeing along the observing nights. We find that the two blazars do not present intra-night photo-polarimetric variability, although we do detect a significant inter-night variability. Comparing polarimetric values before and after accounting for the host galaxies, we observe a significant difference in the polarization degree of about 1% in the case of 1ES 1959+650, and 0.3% in the case of HB89 2201+044, thus evidencing the non-negligible impact introduced by the host galaxies. We note that this host galaxy effect depends on the waveband, and varies with changing seeing conditions, so it should be particularly considered when studying frequency-dependent polarization in blazars.